Stay positive : encouraging quotes and messages to fuel your life with positive energy - Gordon, Jon, 1971-; Decker, Daniel, 1975- (Wiley, 2020)
Fuel yourself and others with positive energy-inspirational quotes and encouraging messages to live by from bestselling author, Jon Gordon. Ever since he wrote the mega bestseller The Energy Bus , Jon Gordon has been sharing inspirational messages and encouragement via his talks, books, and social media posts. After many requests to create a collection of his quotes, Jon teamed up with his long-time friend, Daniel Decker, to create Stay Positive . Stay Positive is more than a book of positive quotes. This book is a resource you can turn to each day for encouragement to help you take on your daily challenges, pursue your goals and dreams, and create positive momentum in your life. The power of positive thoughts is not about being Pollyanna Positive; it's the real stuff that makes a proven difference in your perspective and life. After all, we don't give up because it's hard; we give up because we get discouraged. By fueling yourself with encouragement and positive energy, you'll have greater power to overcome negativity, neutralize the naysayers, and conquer adversity. Stay Positive is more than a phrase. It's an approach to life that says when you get knocked down, you'll get back up and find a way forward one faithful step and optimistic day at a time. Start your day with a message from the book, or pick it up anytime you need a mental boost. You can start from the beginning, or open the book to any page and find a message that speaks to you. However you decide to use Stay Positive , it's a go-to resource for anyone wanting to inject a healthy dose of positivity into their life.